CONTAMINATION OF LETTUCE BY PARASITES IN MUNICIPALITIES IN NORTHWESTERN RIO GRANDE DO SUL, BRAZIL - Graffunder, Karine Gehrke; Buhring, Lilian Ester von Muhlen; Muller, Gerson Azulim (Interfaces Científicas - Saúde e Ambiente, 2019)
Lettuce, one of the vegetables most consumed by people, can serve as a vehicle for various parasites, such as protozoa and helminth worms. The present study aimed to characterize the contamination of lettuce sold in northwestern Rio Grande do Sul, Brazil by parasitic forms potentially infectious to humans. Between August 2015 and July 2016, 320 lettuce samples from eight municipalities in northwestern Rio Grande do Sul were analyzed using the spontaneous sedimentation and centrifugal-flotation methods. Material obtained with these methods was observed under a microscope and the parasites present were identified. Seventy-one samples (22.9%) had at least one parasite group. The following parasites were found: Ancylostomatidae (8.75%), Toxocara spp. (6.87%), Trichuris spp. (6.25%), Toxoplasma gondii (2.19%), Ascaris spp. (1.25%), Entamoeba spp. (0.94%), Giardia spp. (0.94%), Balantidium spp. (0.62%) and Isospora spp. (0.62%). Lettuce sold in the municipalities sampled showed relatively low parasite contamination. However, Brazilian law indicates that only parasite-free vegetables are of adequate quality for consumption. Thus, there is a need for greater sanitary care to avoid fecal contamination of this type of food.